Answer:
The expressions in order from least (1) to greatest (5) based on their values is:
6a − 2b
2a + b
2b + a
4b − a
3(a + b)
Step-by-step explanation:
a = 3 and b = 5
2a + b
2b + a
3(a + b)
4b − a
6a − 2b
Replacing the value of a and b inside the expression we have:
2a + b = 2(3) + 5 = 6 + 5 = 11
2b + a = 2(5) + 3 = 10 + 3 = 13
3(a + b) = 3(3 + 5) = 3(8) = 24
4b − a = 4(5) - 3 = 20 - 3 = 17
6a − 2b = 6(3) - 2(5) = 18 - 10 = 8
The expressions in order from least (1) to greatest (5) based on their values is 8, 11, 13, 17 and 24.